COMPARATIVE METAGENOMIC ANALYSIS OF THE ORAL MICROBIOME IN DIABETIC AND NON-DIABETIC INDIVIDUALS (AUN INTERNATIONAL CONFERENCE, 2025)
Diabetes has been associated with alterations in the oral microbiome, but the specific relationship remains unclear. This study compared the oral microbiomes of 34 diabetic and non-diabetic individuals using oral swab samples. DNA was extracted, quantified, and sequenced with PacBio Sequel IIe technology targeting the 16S rRNA V1–V9 regions. Data were analyzed with QIIME2, and statistical tests assessed diversity and group differences. Results showed that pathogenic genera such as Pseudomonas and Klebsiella were more abundant in diabetics (31.2% vs 18.7% for Pseudomonas). Alpha diversity was lower in diabetic samples (Shannon index 1.58 vs 2.20), though no significant difference in total bacterial abundance was found (p=0.998). Overall, the findings suggest diabetes is linked to shifts in oral microbiome composition, and further research with larger cohorts is needed to confirm these patterns.